The Discharge Companion Program: An Interprofessional Collaboration in Transitional Care Model Delivery - Jennifer Bingham; Patrick Campbell; Kate Schussel; Ann M. Taylor; Kevin Boesen; Amanda Harrington; Sandra Leal; Terri Warholak (MDPI AG, 2019)
To reduce readmission rates and avoid financial penalties from the Centers for Medicare and Medicaid Services, hospitals are seeking to implement innovative transitions of care (TOC) programs. This retrospective study evaluated the Discharge Companion Program (DCP), a pharmacist- and nurse-coordinated interprofessional, collaborative TOC program. Adult patients (18 years and older) from a single hospital, discharged with at least one qualifying diagnosis, were eligible for this service. The hospital transitional care coordinator nurse referred qualified patients to the DCP nurse coordinator, who scheduled telephonic medication therapy management (MTM) reviews with the DCP pharmacist at one- and three-weeks postdischarge. Hospital records and DCP documentation were reviewed to describe respective interventions and assess the impact on 30-day readmissions. A total of 456 patients were referred to the DCP between 31 August, 2015 and 7 September, 2016. Of the 340 patients who participated (DCP group), 44 (13%) compared to 17% (n = 20) of the usual care, were readmitted within 30-days postdischarge. The DCP pharmacists conducted 1242 clinical interventions with participants, demonstrating the benefits of an interprofessional TOC model involving multiple, pharmacist-delivered MTM intervention touchpoints within 30 days post-hospital discharge.